Ulama Hadis dan Orientalis: Analisis Historis tentang Asal Usul Hadis - Alwi Shobri; Pais Ainul Yaqin (Al-Hasyimi: Jurnal Ilmu Hadis, 2024)
The origin of Hadith is a complex and often debated topic in the study of Hadith between traditional scholars and orientalists. According to traditional scholars, Hadith is a record of the life of the Prophet and developed in the period after the death of Prophet Muhammad, when his companions began to transmit it orally. On the other hand, orientalists tend to observe the origin of Hadith with a critical approach, highlighting the historical and cultural contexts that likely influenced its emergence. Based on this, this paper aims to analyze the perspectives of traditional scholars and orientalists on the origin of Hadith, as well as explore the differences and similarities of their perspectives in a historical context. This research uses a qualitative method with a historical and comparative approach. Data were obtained through a literature review of various primary and secondary sources. The results show significant differences between the views of traditional scholars and orientalists regarding the origin of Hadith. Traditional scholars use rigorous and systematic methodology to ensure the historicity and authenticity of Hadith through the verification of the chain of sanad and matan. Conversely, orientalists, while more skeptical, see Hadith as a reflection of the social and political developments of the Muslim community after Prophet Muhammad.